Il personale è politico? Processo di autocolonizzazione e rapporto tra i generi in Frantz Fanon: Is the personal political? Process of self-colonisation and the relationship between genders in Frantz Fanon - Carofalo, Viola (Itinerari, 2023)
This text examines Frantz Fanon’s analysis of the gender relationships under colonialist domination. In order to understand the psychic mechanisms within the dominated subjects in the sexual/sentimental sphere, Fanon, lacking any scientific literature to refer to, bases his analysis (and socio-analysis) on fictional characters of literature. The Martinican psychiatrist, through this analysis of the sentimental and erotic relationship between colonized and colonizing (and colonized among them), identifies the close link between sexual liberation and political liberation. “The atmosphere of violence” that characterizes the colonial context in fact affects the relationship with the other and as well as desire, turning them into subordination and dependence respectively. In this view, according to Fanon, a “balanced” relationship can only take place with the overcoming of colonial domination.